1995
DOI: 10.1149/1.2050083
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Epitaxy Growth of TiN Thin Films

Abstract: AlN thin films were grown by the Atomic Layer E p i t q (ALE) technique employing AIC13 and NH3 as precursors. A growth rate of 1.0 &cycle was obtained in experiments carried out at 500 "C. The films deposited onto soda lime glass substrates were polycrystalline exhibiting a strong preferred orientation in the [OOll direction. X-ray Photoelectron Spectroscopy (XPS) measurements revealed that the films contained oxygen and chlorine as impurities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 9 publications
4
127
0
1
Order By: Relevance
“…[13] The N concentration in the N-TiO 2 is dictated by the competition between H 2 O and NH 3 with the TiCl x surface species to form TiO 2 and TiN, respectively. The overall chemical reactions for these two processes can be represented by ( ) (…”
Section: Doi: 101002/adsu201600041mentioning
confidence: 99%
“…[13] The N concentration in the N-TiO 2 is dictated by the competition between H 2 O and NH 3 with the TiCl x surface species to form TiO 2 and TiN, respectively. The overall chemical reactions for these two processes can be represented by ( ) (…”
Section: Doi: 101002/adsu201600041mentioning
confidence: 99%
“…Nevertheless, in our case, the variation of the lattice parameter is always higher for TiN layers deposited at 500 C according to the second set of deposition parameters than for TiN layers obtained at 800 C according to the first set of deposition parameters. Moreover, in their study, Ritala et al [16] also observed a variation of the lattice parameter dependent on the oxygen contamination. In their study, thermal stresses could be disregarded because the substrate used (soda lime) exhibits a thermal expansion coefficient of 9.2´10 ±6 K…”
Section: ±1mentioning
confidence: 80%
“…Three possibilities can be considered: i) non-stoichiometry of TiN, [14] ii) stresses in the layer, [15] and iii) oxygen contamination. [16] The first point can be dismissed because NRA and RBS analysis always reveal a Ti/N ratio very close to one. For the second point, the variation of the lattice parameter can be due to a development of macrostresses in the layer.…”
Section: The Role Of Oxygen Contaminationmentioning
confidence: 99%
“…[17] For transition metal nitride ALD, metal halides together with ammonia have been the most widely used precursors. [18][19][20][21][22] With the halide-ammonia ALD system, relatively high deposition temperatures, usually 400-600 8C, have to be used and aggressive hydrogen halides are released as a side product. Recently, novel metal-organic precursors containing amido and imido ligands have been introduced for tantalum, [23] tungsten, [24] and molybdenum.…”
Section: Introductionmentioning
confidence: 99%